STUDI PERANCANGAN KAPAL PUSKESMAS KELILING UNTUK MENUNJANG PELAYANAN KESEHATAN DAERAH PESISIR KABUPATEN LEMBATA - Ari Wibawa Budi Santosa; Hizkia Parningotan Pangaribuan; Sarjito Joko Sisworo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The sinking of the floating hospital ship Dr. Lie Dharmawan has hampered health services several operational areas, one of which is Lembata Regency. Health services via ships are very much needed in Lembata Regency because many coastal areas still do not get maximum health services. The purpose of this research is to design a mobile health center ship that can reach coastal residents to get decent and good health services, and it doesn't take a long time to travel to get health services. The main size is obtained through the parent design approach method. Analysis of ship resistance using the holtrop method and ship stability analysis met the IMO stability criteria. Calculation of the profile construction according to the rules of BKI Vol.II which calculates the construction of the hull, deck, bottom, and superstructure. The results of the design of the mobile health center ship are designed with facilities that comply with the standards of the Minister of Health Regulation with a length of 23.13 m LOA, 21.31 m LPP, 20.35 m LWL, 6.82 m width, 1.5 m draft, 4.4 height m, Cb 0.548, speed 12 knots and the estimated cost of building a ship is Rp. 4,032,617,052,04.